Towards ferrous medium-entropy alloys with low-cost and high-performance. (September 2020) - Bae, Jae Wung; Kim, Hyoung Seop
Abstract: This article introduces a practical and straightforward strategy to take a paradigm shift in the high-entropy alloys (HEAs) and medium-entropy alloys (MEAs) design concept from equiatomic alloys towards cost-effective ferrous medium-entropy alloys (FeMEAs). Upon deviating from the equiatomic composition in Fe-containing alloy system, we show that various FeMEAs can be developed by pseudo-binary methods. Further, we discuss an overview of the microstructural evolution and mechanical properties of recently-developed FeMEAs, which exhibit a broad spectrum of microstructures and mechanical properties. This viewpoint article highlights insights into the concept of FeMEAs, providing a potential direction for future development of HEAs and MEAs.